COVID-19 related acute necrotizing encephalopathy with extremely high interleukin-6 and RANBP2 mutation in a patient with recently immunized inactivated virus vaccine and no pulmonary involvement - Thanakit Pongpitakmetha; Pasin Hemachudha; Wanakorn Rattanawong; Poosanu Thanapornsangsuth; Anand Viswanathan; Thiravat Hemachudha (My University, 2022)
Abstract Background We report the first case of COVID-19 associated acute necrotizing encephalopathy (ANE) without pulmonary disease in a patient with an extremely high interleukin-6 (IL-6) level and Ran Binding Protein 2 ( RANBP2 ) mutation. Case presentation A 29-year-old woman recently immunized with inactivated viral vaccine—BBIBP32-CorV (Sinopharm) presented with alteration of consciousness. Her body temperature was 37° Celsius, blood pressure 42/31 mmHg, heart rate 130 bpm, respiratory rate 20 per minute, and oxygen saturation 98%. Respiratory examination was unremarkable. Neurological examination revealed stupor but preserved brainstem reflexes. Non-contrast computerized tomography of the brain showed symmetrical hypodense lesions involving bilateral thalami and cerebellar hemispheres characteristic of ANE. No pulmonary infiltration was found on chest radiograph. SARS-CoV-2 was detected by PCR; whole genome sequencing later confirmed the Delta variant. RANBP2 gene analysis revealed heterozygous Thr585Met mutation. Serum IL-6 was 7390 pg/mL. Urine examination showed pyelonephritis. Her clinical course was complicated by seizure, septic shock, acute kidney injury, and acute hepatic failure. She later developed coma and passed away in 6 days. Conclusions ANE is caused by cytokine storm leading to necrosis and hemorrhage of the brain. IL-6 was deemed as a prognostic factor and a potential treatment target of ANE in previous studies. RANBP2 missense mutation strongly predisposes this condition by affecting mitochondrial function, viral entry, cytokine signaling, immune response, and blood–brain barrier maintenance. Also, inactivated vaccine has been reported to precipitate massive production of cytokines by antibody dependent enhancement (ADE). The true incidence of COVID-19 associated ANE is not known as were the predictors of its development. We proposed these potential two factors ( RANBP2 mutation and ADE) that could participate in the pathogenesis of ANE in COVID-19 apart from SARS-CoV2 infection by itself. Further study is needed to confirm this hypothesis, specifically in the post-vaccination period. Role of RANBP2 mutation and its application in COVID-19 and ANE should be further elaborated.
Keywords: Infectious Encephalopathies and Encephalitis